Life cycle assessment of reusing by-products from esterification reaction: Through the acidification process - Anggara Dwita Burmana; Rondang Tambun; Renita Manurung; Maya Sarah; Bode Haryanto; Iriany; Ruri Rizki Syahputri Zuhri (Results in Engineering, 2025)
This study aims to investigate the results of biodiesel synthesis utilizing Amberlite 14i and the acidification process applied to the effluent from the process using 12 different scenarios. Reusing the catalyst up to 19 times was the outcome of the esterification process with constant nitrogen stirring. Utilizing treated wastewater lessens the pressure on water supplies, which is important in areas with limited water supplies. The assessment's findings illustrate the environmental effects linked to the production of one kilogram of biodiesel. These effects include eutrophication (0.0004 kg of PO4 equivalent), acidification (0.0082 kg of SO2 equivalent), and the possibility of global warming (1.0382 kg of CO2 equivalent). The investigation of the acidification process with 3 different types of strong acids on the by-products of esterification reactions utilizing homogeneous and heterogeneous catalysts is what makes this study novel. The results indicate that, in comparison to other scenarios, scenario 8 (heterogeneous catalyst, 0.5% NaOH; 5% HCl) has the best acidification process, which is also reasonably inexpensive and produces less waste.